GUIDING THE NEW GENERATION: MUSYRIFAH PSYCHOLOGICAL READINESS IN SUPPORT THE ADAPTATION OF SANTRI AT PESANTREN - Sa'diah, Halimatus; Mumbaasithoh, Layli; Lidyawangi, Syifa Cemara (Jurnal At-Taujih, 2025)
Abstract The adaptation process is an essential and inevitable phase that all new santri undergo. However, some santri experience significant challenges in navigating their first year. During this critical period, institutional support from pesantren administrators becomes vital. The musyrifah—female santri mentors assigned to accompany new santri—play a crucial role in facilitating a smooth adaptation process. This study aims to examine the psychological readiness of musyrifah in supporting new santri during their initial year. The participants consisted of 54 female musyrifah tasked with mentoring incoming santri. Data were collected through face-to-face interviews focusing on the musyrifah's preparedness to fulfill their mentoring responsibilities. The findings indicate that the musyrifah possess a high level of psychological readiness, encompassing five key dimensions: cognitive readiness, emotional readiness, moral readiness, behavioral readiness, and exemplary conduct. Abstrak Proses adaptasi pada dasarnya adalah masa yang selalu dilalui santri baru. Namun, terdapat beberapa santri baru yang kesulitan melalui tahun pertamanya. Para santri baru membutuhkan dampingan dari pengurus pesantren dalam proses adaptasi. Musyrifah sebagai pendamping santri baru merupakan harapan besar untuk mendukung proses adaptasi santri baru dengan baik. Fokus penelitian ini guna melihat gambaran kesiapan psikologis musyrifah mendampingi santri baru di tahun pertama. Partisipan merupakan musyrifah atau pendamping santri baru dengan total partisipan sebanyak 54 santri perempuan. Pengumpulan data dilakukan dengan wawancara tatap muka terkait kesiapan para musyrifah mendampingi santri baru. Hasilnya, terdapat gambaran bahwa pendamping santri atau musyrifah memiliki kesiapan psikologis yang penuh, yang menggambarkan kesiapan kognitif, kesiapan emosi, kesiapan moral, kesiapan perilaku, dan kesiapan keteladanan.